Pembangunan Ekonomi Inklusif Melalui Nilai Islam dan Kearifan Lokal - Makki, Mustaqim; Azisi, Azisi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study examines the development of inclusive economy in the mualaf community through the application of Islamic values and local wisdom, with a case study of the Alyumna Candi Kuning Foundation in Bali. Previous studies have less explored the mualaf community in the context of economic development, especially in non-Muslim areas such as Candi Kuning Bedugul, thus this study fills this gap. This research offers a new approach by combining Islamic values, such as the development of inclusive economic empowerment, the contribution of zakat and infaq implementation concepts, and Balinese local wisdom such as gotong royong and tri hita karana to strengthen the economy of the mualaf community. The research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, field observations, and document analysis. Thematic analysis was used to understand the application of Islamic values and local wisdom in economic mentoring activities for the mualaf community. The research shows that the integration of religious values and local wisdom can strengthen the community economy, create social solidarity, and support inclusive economic development. The religion and local culture-based approach has proven effective in addressing the economic challenges of the Alyumna Foundation's mualaf community. Research recommendations include the development of policies that support inclusive economic models based on religious and local cultural values. Governments and organizations can adopt this approach to assist other communities in Indonesia.